Inhomogeneity of dielectric properties of cadmium zinc-telluride crystals grown from melt - Poluboiarov, O.O.; Chugai, O.N.; Voloshin, O.O.; Zherebyatiev, D.P.; Oleynick, S.V.; Sulima, S.V. (Functional Materials, 2016)
Dielectric properties of Cd₁₋xZnxTe crystals made from different ingot regions were investigated in a low-frequency region. Wavelet analysis was used for take-off of regular component in dependence of both parts of dielectric permittivity from spatial coordinate. It is ascertained that dielectric response of crystals has a relaxational character. Regular changes of response characteristics in ingot growth direction were revealed. Such peculiarities of properties are explained with changes during growth process not only in ratio of solid solution basic components, but also of intrinsic structure defects, especially related with cadmium vacancies.